Social commentary in the song “Chineke doo” by Sam Ojukwu - Sunday Ofuani; Comfort Onyekachukwu Ofuani (Tydskrif vir Letterkunde)
Early art music in Nigeria was not based on nor conceived as a medium for social commentary. However, through cultural reawakening, contemporary Nigerian-Igbo composers now deliberately utilise social commentary themes in their music. This practice enhances their musical works as social-cum-functional art—a notable essence of music in traditional Africa. There is a dearth of studies on Igbo art music composers and social commentary. In this study, we focus on Sam Ojukwu and his composition “Chineke doo” (A prayer for Nigeria) to explicate the compositional utility of social commentary themes in the Nigerian-Igbo context. The selection of the piece is based on its social relevance and the composer’s creativity, output, and consistency in social commentary art music. Textual data extracted from the piece and an interview with the composer provided the primary data for the study. Altogether, we discuss the contemporary Nigerian socio-political ironies recreated in “Chineke doo”. Through the socio-cultural context, along with suitable musical text examples, we deepen the understanding and appreciation of how social commentary in music relates to specific social and political issues in Nigeria. The study is significant in the evaluation, appreciation, and justification of Ojukwu as a music-composer-social-commentator and poet who thrives in social commentary art music compositions for the sake of societal engineering and transformation.